THE HEMORRHAGIC AREA OF THE PACIENT, CANDIDATE FOR ORAL SURGERY AND THE EXISTING RISKS - Kamel Earar; Gabi Topor; Cristian Constantin Budacu; Laura Rebegea; Dorel Firescu (Romanian Society of Oral Rehabilitation, 2021)
The deepest knowledge of the patient's field allows the nuance of the explorations, of the indications of pre-anesthetic training, of the prognostic formulations and of course the avoidance of the erroneous recommendations.Rigorous medical history, complete organic examination, general biological examinations actually perform the assessment of the patient's terrain and not a proper diagnosis of the disease itself . If from the interpretation of these data appears a field with significant deviations from normal, more complex investigations are recommended in clinics or specialized laboratories and only with a close interdisciplinary collaboration (internist, cardiologist, diabetologist, allergist, etc.) anesthesia behavior is established and also the time, place and extent of surgery. Hemorrhage, intravascular thrombosis and embolism are common clinical manifestations of many diseases. Normal hemostasis limits blood loss through precisely regulated interactions between vascular wall components, platelets, and plasma proteins. Knowledge of these conditions and the mechanisms that produce them is important due to their interference with dental therapy and oral surgery